ChemInform Abstract: Crystal Structure and Luminescence Properties of a Novel Red‐Emitting Phosphor BaAlBO3F2:Eu3+. Issue 46 (18th November 2014) - Chen, Wanping; Zhou, Ahong; Liu, Yan; Dai, Xiaoyan; Yang, Xin
Abstract BaAlBO3F2:xEu3+ (0.001 ≤ x ≤ 0.08) phosphors are synthesized by solid state reaction of Al2O3, Eu2O3, H3BO3, BaCO3, and NH4F (air, 850 °C, 5 h).